Pre-exposure to Tempting Food Reduces Subsequent Snack Consumption in Healthy-Weight but Not in Obese-Weight Individuals - Stamos, Angelos; Goddyn, Hannelore; Andronikidis, Andreas; Dewitte, Siegfried (Frontiers in Psychology, 2018)
Obesity has become a severe worldwide problem. Compared to healthy-weight individuals, obese individuals seem to show an increased sensitivity to tempting food. In the present study we test pre-exposure effect which implies that consumption of tempting food is decreased after exposure to tempting food cues in a context of a task that discourages food consumption. Healthy-weight and obese-weight participants were recruited via social media and university channels. Participants took part in a scrabble task with either candy letters or foam letters and subsequently engaged in a taste test. Results showed that in healthy-weight participants, consumption was reduced after solving the scrabble task with candy letters in comparison to foam letters. In obese-weight participants, consumption was reduced in the condition using foam letters (in comparison with healthy-weight participants). The pre-exposure effect was replicated in healthy-weight participants, but could not be observed in participants with obesity, since consumption was reduced in general in this group. Our results suggest that more work should be done to understand how food nudges work in the context of obesity.